Long-term treatment with finasteride induces apoptosis and pathological changes in female mice. (July 2019) - Alkahtane, AA; Albasher, G; Al-Sultan, NK; Alqahtani, WS; Alarifi, S; Almeer, RS; Alghamdi, J; Ali, D; Alahmari, A; Alkahtani, S
Androgenetic alopecia is the most common type of alopecia, and it affects humans of both genders. Finasteride is a type II selective 5α-reductase inhibitor that is administered orally to treat androgenetic alopecia and benign prostatic hyperplasia in human males. However, its effect on the vital organs of females is unknown. This study was designed to investigate the effects of finasteride on the vital organs such as liver, kidney, and heart of female mice. To study the prospective effects of finasteride, female mice were orally administered two doses of finasteride (0.5 and 1.5 mg/kg) once daily for 35 days, and serum levels of various biochemical parameters and histopathology of various organs were examined. The results showed that serum levels of alkaline phosphatase were significantly increased by both high- and low-dose finasteride, whereas cholesterol was significantly increased by the high dose only. Creatine kinase was significantly increased by the high and low doses, whereas glucose was significantly decreased by both doses. Histopathological analysis and DNA damage assays showed that finasteride has adverse effects within both the short and the long periods in female mice. In addition, the proapoptotic genes Bax and caspase-3 were significantly increased by high dose finasteride, whereas the antiapoptotic gene Bcl-2 was significantly decreased by the low and high doses. In conclusion, finasteride is not currently approved for therapeutic use in females, and the findings in this study suggest caution in any future consideration of such use.